KINERJA GURU DALAM PENGELOLAAN PEMBELAJARAN DI SMK PEMDA PADANG PANJANG - Puji Astowo (Universitas Negeri Padang, 2013)
This research is motivated by not maximal in the management of learning teacher at Government Secondary School Vocational pemda padang panjang. This study aimed to obtain information about the performance of the teacher in the management of learning. This study is a descriptive study population of all public elementary school teachers in Government Vocational School Long prairie, for the sample is 30 people. Data collection tool was a questionnaire Likert scale models that have been tested for validity and realibility. The data were processed using the formula mean. The results concluded general management of learning in vocational high school government long meadow is in the category quite well with an average score of 3.85 with the achievement levels reached 77%. Thus it can be said that the performance management of teachers in vocational schools teaching in the pemda padang panjang government done pretty well and hopefully all vocational high school teachers in the pemda padang panjang government can improve its performance in the management of learning in order to get a quality learning outcomes. Key word: Management of learningby teacher